2012
DOI: 10.1136/bmjopen-2012-001477
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes: a cohort study of treatment, ethnic and social group influences on glycated haemoglobin

Abstract: ObjectivesTo assess whether in people with poorly controlled type 2 diabetes (HbA1c>7.5%) improvement in HbA1c varies by ethnic and social group.DesignProspective 2-year cohort of type 2 diabetes treated in general practice.Setting and participantsAll patients with type 2 diabetes in 100 of the 101 general practices in two London boroughs. The sample consisted of an ethnically diverse group with uncontrolled type 2 diabetes aged 37–71 years in 2007 and with HbA1c recording in 2008–2009.Outcome measureChange fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…After screening the titles and abstracts of all references, 262 potentially eligible articles were read full text. Fifty‐five studies met the inclusion criteria of this review . As 2 studies examined identical associations within the same sample, we only included 1 paper in our study .…”
Section: Resultsmentioning
confidence: 99%
“…After screening the titles and abstracts of all references, 262 potentially eligible articles were read full text. Fifty‐five studies met the inclusion criteria of this review . As 2 studies examined identical associations within the same sample, we only included 1 paper in our study .…”
Section: Resultsmentioning
confidence: 99%
“…Despite the heterogeneous nature of HbA1c progression in T2DM, trajectories tended to vary according to baseline HbA1c, treatment group and patient age. The systematic literature review additionally identified a small number of studies that examined ethnic differences and gender differences in HbA1c progression in T2DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Initial monotherapy took place at a mean HbA1c of 8% (−0.9% reduction), mean time to dual therapy was 2.6 years (HbA1c at 8.5%; −1.1% reduction observed), and mean time to insulin initiation was 7 years (HbA1c at 9.8%; −1.5% reduction observed). Figure 3 10 Price et al 11 Sun et al 12 Virdi et al 13 Year 2010 a small number of studies that examined ethnic differences [14][15][16][17][18][19] and gender differences 14,[19][20][21] in HbA1c progression in T2DM patients.…”
Section: Illustrative Analysismentioning
confidence: 99%
“…(19) In addition, a more recent prospective cohort study showed that South Asians with poorly controlled DM are less likely to achieve controlled HbA1c and respond less favourably to treatment in terms of HbA1c levels. (20) While it is unclear whether these findings can be extrapolated to inpatients in an acute care setting, it suggests that HbA1c alone is not a good indicator of the intensity of treatment required and that clinicians should utilise other indicators (e.g. BG levels) to guide glycaemic management.…”
Section: Discussionmentioning
confidence: 99%